Targeting ADG of Developing Replacement Heifers Using Age and Body Weight - John Arthington; Philipe Moriel (EDIS)
This publication was prepared to assist beef cattle producers and livestock agents in determining the target ADG and management system to develop replacement beef heifers in Florida. Written by John Arthington and Philipe Moriel, and published by the UF/IFAS Department of Animal Sciences, revised October 2021.